Design of broadband class-F power amplifier with high-order harmonic suppression for S-band application - 林俊明 章国豪 郑耀华 李思臻 张志浩 陈思弟 (Journal of semiconductors, 2015)
A broadband class-F power amplifier for an S-band handset device is integrated on a 330.82 mm^3 die using an In Ga /GaAs HBT process. With LC serial harmonic traps immersed into the broadband output matching circuit, good harmonic suppression performance can be achieved. A pure resistive impedance of the matching circuit, but near zero at second and infinite at third harmonic frequency, which enhances the efficiency, is obtained across 1.8–2.5 GHz. Tested with a continuous wave（CW） signal, the PA delivers an output power of 34 dBm and achieves a PAE of 57% at 2 GHz. In addition, excellent harmonic suppression levels of less than –53 dBc across the second to fifth harmonic are obtained.